Integrated supply chain projects and multifunctional local development: The creation of a Perfume Valley in Tuscany - Silvia Scaramuzzi; Giovanni Belletti; Paola Biagioni (Agricultural and Food Economics, 2020)
Marginal rural areas are undergoing major pressures from the effects of globalization, especially when no alternative has been found to conventional extensive agriculture and a lack of investments and vision squeezes the income of farmers. The objective of the paper is to show how Integrated Supply Chain Projects (Progetti Integrati di Filiera (PIF)), Italian rural policy tools funded in the framework of EU's Rural Development Policy, can integrate supply chain innovation and territorial integrated strategies, fostering a multifunctional development of marginal rural areas towards a newly discovered identity. The case study is the PIF "Flora Aromatica Santa Luce" funded by the Tuscany Regional Administration RDP in 2016. The project aims at creating a new supply chain of organic aromatic plants in the Santa Luce Valley (PI). The integration is based, on the one side, on the creation and valorization of the new supply chain product, represented by an organic cosmetic line made with lavender essential oil, and, on the other side, on the territorial development of the Valley, in an economic, social, environmental and touristic perspective. From a theoretical point of view, the approach used was based on the new rural development paradigm, assuming that the processes of broadening, deepening and regrounding, together compose the main axis of rural development. The canvas model was used in order to identify a business model for the new supply chain and the territorial development of the area, while, at the methodological level, a participatory action research (PAR) approach was adopted. Results show how a supply chain project (like a PIF) can enhance innovation and stable commercial relationships within the supply chain and support processes of vertical and horizontal coordination, but also stimulate extended territorial strategies supporting the integration processes between agriculture, processing and other economic activities following a territorial multifunctional development logic. At the same time, key benefits for the policymaker and local administrations can also be identified in particular for marginal rural areas where farmers and other local actors are weaker and collective action is more difficult. Thanks to the PAR approach, a PIF can stimulate participation of farmers to relevant RDP measures but also allow convergence of individual actions towards wider regional and local strategic objectives.
Keywords: 330; Local development; Integrated Supply Chain Project; Multifunctionality; Rural development policy; Rural tourism; Business Model Canvas; Officinal plants; Lavender